Collision of a ball with the edge of a step. (11th October 2019) - Cross, Rod; Lindsey, Crawford
Abstract: An experiment is described where a rubber ball was incident on the edge of a step to simulate the impact of a sports ball with a sharp edge. Measurements of the rebound speed, angle and spin indicated that the impact was equivalent to one with an inclined plane. The incline angle depends not only on the impact point on the ball but also on the rotation angle of the ball during the impact. Results are presented for cases where the ball was incident vertically on the step and also obliquely.